Analisis Metode Projected Unit Credit dan Entry Age Normal dalam Perhitungan Aktuaria Dana Pensiun dengan Suku Bunga Konstan dan Model Vasicek - Mutalip, Nurqalbu Abd.; Kartikasari, Mujiati Dwi (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
Retirement planning requires strong financial preparedness, making pension funds a crucial component of long-term financial strategies. One of the key aspects in managing pension funds is the actuarial method used to calculate pension liabilities and contributions. This study aims to compare the normal cost and actuarial liability calculations between two actuarial methods, namely Projected Unit Credit (PUC) and Entry Age Normal (EAN), under two interest rate assumptions: a constant interest rate and a stochastic interest rate modelled using the Vasicek model. The Vasicek model is applied to capture the dynamic fluctuations in interest rates, providing more realistic estimates. Based on parameter estimation, the stochastic interest rate obtained through the Vasicek model is 7.113%. The results show that applying the Vasicek model leads to higher actuarial liabilities compared to the constant interest rate approach. Furthermore, the EAN method results in lower final contributions and higher actuarial liabilities compared to the PUC method, making it more favourable for pension participants. These findings highlight the importance of considering interest rate dynamics in pension valuation to enhance the accuracy and relevance of actuarial calculations in an ever-changing economic environment.